From Hashtags to Economic Shock: Digital Mobilization & Business Disruption during Nepal’s Gen-Z Protest - K.C., Subekshya (Apex Journal of Business and Management, 2026)
In Nepal, the September 2025 Gen-Z protests marked a pivotal shift in the nation’s political and economic landscape. Sparked by entrenched issues of corruption, governance failures, and accountability deficits, this digitally mobilized youth movement evolved into one of the largest uprisings in recent history. This study examines how online coordination transitioned into profound economic disruptions, including declines in foreign direct investment (FDI), banking operations, stock market performance, and tourism revenues. Employing a qualitative approach, the research draws on secondary data from government reports, financial metrics, and media analyses. It is complemented by semi-structured interviews with 12 stakeholders directly or indirectly impacted by the unrest, providing nuanced contextual insights. Findings reveal that while digital platforms accelerated mobilization, economic fallout stemmed primarily from amplified uncertainty and perceptual risks. Notable drops in FDI pledges, market capitalization, tourist arrivals, and credit growth underscore the rapid erosion of investor confidence. The protests exposed institutional frailties beyond mere technological curbs, signaling deep societal discontent. This paper bridges digital activism with macroeconomic effects, enriching literature on generational dynamics. It advocates governance reforms, enhanced transparency, and proactive risk strategies to safeguard stability in volatile settings.